2007
DOI: 10.1016/j.jvs.2006.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Association of obesity and metabolic syndrome with the severity and outcome of intermittent claudication

Abstract: These findings, if confirmed in other cohorts, suggest the importance of treating obesity in patients with intermittent claudication. Serum adiponectin concentrations may be an important guide to the efficacy of treatment in patients with intermittent claudication and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 35 publications
6
88
2
Order By: Relevance
“…It is well established that obesity is a risk factor for the development of PAD [26]. However, the incidences of obesity did not differ between the subjects with and without PAD in the current study.…”
Section: Discussioncontrasting
confidence: 74%
“…It is well established that obesity is a risk factor for the development of PAD [26]. However, the incidences of obesity did not differ between the subjects with and without PAD in the current study.…”
Section: Discussioncontrasting
confidence: 74%
“…37 Previous studies Very little is known about the relationship between obesity and cardiovascular risk in PAD, and no study has compared the effect of different anthropometric measures on outcome. In 61 patients with intermittent claudication, Golledge et al 21 found that the incidence of cardiovascular events at 24 months was higher in patients with central obesity defined using the International Diabetes Federation criteria than in patients without this diagnosis (42.8 ± 9.1 vs 11.2±6.1%). Probably due to the small number of patients and events, the authors did not report the statistical significance of their findings.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Obesity, which is associated with inflammation and metabolic syndrome, 16,17 conditions portending a worse outcome in PAD, [18][19][20][21] may be particularly detrimental for cardiovascular risk in affected individuals. Nevertheless, very few studies have investigated the relationship between obesity and occurrence of cardiovascular events in PAD; moreover, with conflicting results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective study showed that high plasma adiponectin levels were associated with a lower risk of myocardial infarction in healthy men, independent of CRP level or glycemic status [49]. In addition, in patients with peripheral arterial disease, serum adiponectin was positively correlated with the ankle-brachial pressure index, maximum walking distance, and initial claudication distance [50], and in another study, serum levels were negatively correlated with the Fontaine stage [51].…”
Section: The Role Of Adiponectin In Metabolic Syndrome and Cardiometamentioning
confidence: 97%